A numerical–analytical study to determine a suitable distribution of plies in sandwich structures subjected to high-velocity impact. (1st March 2023) - Alonso, L.; Solis, A.; García-Castillo, S.K.
Abstract: This work presents a study that was undertaken to find the configuration that corresponds to the highest ballistic limit for composite sandwich structures made of glass fibre-reinforced polymer (GFRP) sandwich skins and a crushable foam. To this end, a new three-dimensional finite element (FE) model was implemented. The model accounts for the constitutive response of the GFRP sandwich skins and the crushable foam by means of two subroutines. A previously developed analytical model was used to support and complete the results of the FE model. Experimental data were also used to validate both models in the vicinity of the ballistic limit for the neutral configuration (same number of plies on the front and rear face skins). Thus, the most appropriate configuration to improve the ballistic limit for a structure with the same material (same number of plies) was obtained by testing different distributions of laminae. The ballistic limit was then estimated for all the possible configurations and the energy-absorption mechanisms were analysed to reveal new insights into the behaviour of these structures when the neutral configuration is varied. In addition, the damaged areas of the specimens were compared between the experiments and the model. As a result, the most suitable configuration turned out to be associated with thicker rear face skins, which produce higher ballistic limits. The largest fraction of the energy was absorbed by the out-of-plane mechanisms, this behaviour being maintained in all the configurations. Experimental observations established that the damaged area of the front face skin was smaller than the damage produced in the rear face skin and that bending effects were notable in the latter. The affected areas were proved to have a round shape, presenting the largest size in the vicinity of the ballistic limit. Highlights: A configuration sensitivity analysis on woven E-Glass Fibre/Polyester peels and PVC foam core is presented. Numerical, analytical and experimental results are compared in order to validate the study. The study predicts a sandwich convenient configuration in terms of the ballistic response. The preponderant role of the back peel is established due to the bending effects.